2011
DOI: 10.3928/15394492-20110513-02
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing, Physiological Stress, and Sleep Behaviors in Children with and without Autism Spectrum Disorders

Abstract: Sleep problems have been frequently identified in children with autism spectrum disorders (ASD). It has been proposed that some sleep problems are due to sensory sensitivity. The purpose of this study was to examine the relationship between physiologic responses to sensation and sleep in children with and without ASD. Fifty-five children participated in the study (ASD, n = 27; typical, n = 28). All children participated in a sensory challenge laboratory protocol. Electrodermal reactivity and salivary cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 49 publications
5
76
0
1
Order By: Relevance
“…In twelve papers (Baranek et al 2013;Boyd et al 2010;Brock et al 2012;Gal et al 2010;Green et al 2012;Hilton et al 2007;Lane et al 2010;Lane et al 2012, Liss et al 2006Nadon et al 2011;Reynolds et al 2012;Samson et al 2013) investigation of associations between sensory processing patterns and a single psychological construct were carried out. Three of these papers have multiple hypotheses on the sub-constructs of the phenomenon under investigation that were tested.…”
Section: Results -Associationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In twelve papers (Baranek et al 2013;Boyd et al 2010;Brock et al 2012;Gal et al 2010;Green et al 2012;Hilton et al 2007;Lane et al 2010;Lane et al 2012, Liss et al 2006Nadon et al 2011;Reynolds et al 2012;Samson et al 2013) investigation of associations between sensory processing patterns and a single psychological construct were carried out. Three of these papers have multiple hypotheses on the sub-constructs of the phenomenon under investigation that were tested.…”
Section: Results -Associationsmentioning
confidence: 99%
“…However, sample characteristics were not always well described. Three studies (Lane et al 2012;Liss et al 2006;Tseng et al 2011) reported only gender and age of their participants. Only Nadon et al (2011) provided all the demographics selected in the evaluation grid characteristics (e.g.…”
Section: Participants' Sectionmentioning
confidence: 99%
See 3 more Smart Citations